PENGARUH PROBLEM BASED LEARNING BEBANTUAN MEDIA LEPO TERHADAP KEAKTIFAN DAN HASIL BELAJAR PENDIDIKAN PANCASILA PESERTA DIDIK KELAS IVA SDIT BUNAYYA: Penelitian Kuantitatif - Wisnu Aji Suryo Anggono; Zahwa En Najmia; Susilo Tri Widodo; Nur Indah Wahyuni; Ismiatul Fauziah (STKIP Subang, 2023)
This research is quantitative research carried out over two cycles and uses quantitative descriptive data analysis techniques on 20 students in class IVA at Bunayya Integrated Islamic Elementary School. The PBL (Problem Based Learning) mode1 is used with the he1p of LePo media. This research focuses on learning activitiies and learning outcomes. Data was collected through observation sheets, tests, interviews and documentation. The percentage of each indicator is calculated for the technical observation sheet, and the average value is calculated for the performance test. The research resu1ts show that the app1ication of the PBL learning model with the he1p of LePo media increases active learning and learning outcomes. The research results showed that the averrage percentage increase in student activity in the first session data was 82% and increased to 97% in the second session. The average academic score in the first session was 71 and increased to 78 in the second session. Therefore, it can be said that the 1earning carried out in this class has succeeded in increasing the learning activities and 1earning outcomes of students in the Pancasila and Citizenship Education subjects in class IVA at Bunayya Integrated Islamic Elementary School because they have achieved the specifieds success criteria.